Brushed Aside: The Untold Story of Women in Art - Charney, Noah (Rowman & Littlefield Publishers, 2023)
Discover anew the herstory of art that Publishers Weekly calls "illuminating" and Foreword Reviews calls "spirited" for an enlightening art history read. How many female artists can you name? Frida Kahlo, Georgia O’Keeffe, Marina Abramovic? How about female artists who lived prior to the Modern era? Maybe Artemisia Gentileschi and then… even a regular museum-goer might run out of steam. What about female curators, critics, patrons, collectors, muses, models and art influencers? This book provides a 360 degree look at the role, influence, and empowerment of women through art—including women artists, but going beyond those who have taken up a brush or a chisel. In 1971, Linda Nochlin published a famous essay, “Why Have There Been No Great Women Artists?” This book responds to it by showing that not only have there been scores of great women artists throughout history, but that great women have shaped the story of art. The result is a book that sheds light on the art world in a very new way, finally celebrating the great women artists and influencers who deserve to be much better known. The entire history of art can be told as a herstory of art.